EKSPLORASI KEBUTUHAN STAKEHOLDERS TERHADAP INFORMASI DALAM PELAPORAN KEUANGAN PEMERINTAH DAERAH - Siska Yulia Defitri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
This research’s aim is to know the perception of stakeholders toward information in financial reporting of local government can fulfil their requirement of financial information. This research also Examination of addition performed in this research is to know influence of respondent characteristic to each requirement variable by consumer of information in financial reporting of local government. The hypothesis of this research is that information published in financial reporting of local government requirement the stakeholders, about is the compliance to the rules, financial information, planning and budgeting, narrative information, economic condition and performance, this research’s subjects are stakeholders of local government cover the secretary of local government, investor, creditor, local government. Data were collected with the method of purposive sampling with respondent in Sumatera Barat. Statistical methods used is test of mean instrument, rank of mean test, a Manova test.The Result indicate that first information requirement and important of stakeholder is financial information, economic condition, performed information planning. Narrative information, and last information the compliance to the rules, narrate, Respondent characteristic that is education storey; level and education background simultaneously have an effect on to requirement of information in financial reporting of local government. This matter indicate that requirement of stakeholder financial reporting of local government differs to be influenced by responder characteristic mount education background and education.